HIV infection among patients with pulmonary tuberculosis in Nigeria (2005)
Respiratory problems like Pneumocystic carinni and Pulmonary tuberculosis (PTB) are among the common opportunistic infections in patients with HIV/AIDS. The risk of acquiring Mycobacterium tuberculosis in a community becomes greater with increase in the number of HIV positive persons with active tuberculosis. This study was carried out to determine the magnitude of HIV infection among PTB patients in different parts of Nigeria as part of the year 2000 national HIV surveillance programme. Blood samples were collected on blotting paper from a total of 2826 individuals attending TB clinics between 1st of September and 1st November, 2000. Samples were collected from patients with confirmed PTB from 12 states in the 6 geopolitical/health zone (2 states/zone) of Nigeria as part of high risk sentinel population groups. Samples were tested for the presence of HIV antibodies using commercial ELISA (Genescreen HIV-1/2, Sanofi Pasteur, Paris). All initially reactive samples were retested with a rapid EIA (Gene II, Sanofi Pasteur, Paris) according to the WHO recommendations (option II). HIV Prevalence in the states varied from 4.2% in Oyo to 35.1% in Benue States with a median prevalence of 17.0%. HIV Prevalence increased with age to a peak of 23.9% among PTB patients 30-39 years and then declined progressively to 12.8% among those 60 years and above. A relatively high HIV infection rate (13.8%) was found among the young adolescent age group 10-19 years. There was no significant difference in the rate among male and female PTB patients tested. Comparison with results of previous HIV sero-surveys shows a steady increase in HIV prevalence among PTB patients over the years. The high prevalence of HIV among young PTB patients aged 10-19 years in this study is worrisome and must be noted for intervention.